Composition, Performance, Reception: Studies in the Creative Process in Music - Thomas, Wyndham (Aldershot Ashgate, 1998)
Composers, performers, listeners, critics and theorists all play vital roles in the creation of music culture; yet often each group can appear to hold widely divergent views of a musical works aims and effects. As the title indicates, this book examines the parts played by these groups and the interaction between them. In the first of eleven essays, Robert Saxton discusses the difficulty in pin-pointing the moment of inspiration for a new composition; while Raymond Warren looks at the problems facing operatic performers, including those that arise when interpretations are suggested by the libretto but not in the music. The changing perception of the composer's art from the 14th century to the present day is charted by Wyndham Thomas, in particular attitudes towards arrangement. Two quite different views of the performers responsibility in communicating the composers intentions are taken by Charles Rosen and Susan Bradshaw, the latter arguing for the need to bridge the gap between theoretical and practical analysis of a work; and in two fascinating case studies, Eric Clarke and Jennifer Davidson highlight the ways in which attention to movements of the body in performance can reveal aspects of musical structure. The reception of music is tackled from a variety of perspectives in the book. In his assessment of audience reaction to Jonathan Harveys The Riot, Adrian Beaumont concludes that our response is influenced by a complex web of expectations and previous musical experience. The influence of record sleeves in also determining a listeners response to music is discussed by Nicholas Cook; while Stephen Walsh and Adrian Thomas explore two milieux of critical reception - the first to the music of Stravinsky, and the second to works composed during the social-realist period in Poland. On a more personal level, Bojan Bujics essay forms a fitting counterpart to Saxtons in his attempt to locate the ways in which we experience a new musical work. These absorbing essays offer new insights into our understanding of music making in all its senses, and suggest future ways of approaching works whether as a composer, performers or listener.Contents: Preface Jonathan Harvey; Introduction Wyndham Thomas; The Process of Composition from Detection to Confection Robert Saxton; The Composer and Opera Performance Raymond Warren; Composing, Arranging and Editing: A Historical Survey Wyndham Thomas; A Performers Responsibility Susan Bradshaw; Freedom of Interpretation in Twentieth-Century Music Charles Rosen; The Body in Performance Eric Clarke and Jane Davidson; Expectation and Interpretation in the Reception of New Music: A Case Study Adrian Beaumont; The Domestic Gesamtkunstwerk, or Record Sleeves and Reception Nicholas Cook; Form and Forming: From Victorian Aesthetics to the Mid-twentieth-Century Avant-Garde Bojan Bujic; Stravinsky and the Vicious Circle: Some Remarks about the Composer and the Press Stephen Walsh; Mobilising our Man: Politics and Music in Poland during the Decade after World War II Adrian Thomas; Notes; Lists of Examples and Illustrations; Contributors Details; Index.Reviews: this book is definitely recommended...the catholic range of this volume will present much material. And if you are curious about what composers and performers say they do, then buy this book. Musical Times
Keywords: Composing; Performance; Audience